2017
DOI: 10.1002/mc.22760
|View full text |Cite
|
Sign up to set email alerts
|

Mouse double minute 4 variants modify susceptibility to risk of recurrence in patients with squamous cell carcinoma of the oropharynx

Abstract: Given the crucial role of Mouse double minute 4 (MDM4) oncoprotein in p53 pathway, single nucleotide polymorphisms (SNPs) could serve as such biomarkers for prediction of SCCOP recurrence. Thus, we investigated associations between three tagging putatively functional variants of MDM4, two in the 3' untranslated region of 3' UTR [rs11801299 (NC_000001.10:g.204529084G>A) and rs10900598(NC_000001.10:g.204525568G>T)] and one in intron 1 [rs1380576(NC_000001.10:g.204488278G>C)], and recurrence risk of SCCOP in 1,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This current study found that MDM4 rs4245739 was associated with tumor HPV16 status in SCCOP. Although we and others have reported associations of some MDM4 genetic variants with risk and outcomes of head and neck cancers or HPV‐associated head and neck cancers, no studies have been focused on this functional polymorphism. Additionally, most of previous studies either had different HPV16 status of study patients or had heterogeneous tumor sites .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This current study found that MDM4 rs4245739 was associated with tumor HPV16 status in SCCOP. Although we and others have reported associations of some MDM4 genetic variants with risk and outcomes of head and neck cancers or HPV‐associated head and neck cancers, no studies have been focused on this functional polymorphism. Additionally, most of previous studies either had different HPV16 status of study patients or had heterogeneous tumor sites .…”
Section: Discussionmentioning
confidence: 90%
“…The univariate prognostic analysis was not statistically significant for some variables, while these variables were retained in the main‐effects and final multivariable model because of biological, epidemiological, and clinical significance considerations. We employed the dominant mode of genotype coding a priori for the SNP analysis as done in our previous analyses and publications . The Kaplan‐Meier method was used to compare survival between patients with different genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined, these miRs presumably down-regulate 157 gene targets, many with well documented roles in cell proliferation, signal transduction, DNA damage response, cancer stemness, adhesion, extracellular matrix (EMT) organization, and genome stability (i.e., MDM4, CDK4, MSH6, XIAP, ETS1, RHOA, SMAD4, POLD3, COL3A1, FGF2, FOXF2, and SOX5). Notably, MDM4 plays a role in regulating p53 and has been linked to cancer recurrence and poor outcomes in HNC patients [89][90][91]. As another example, the transcription of CDK4 is linked to tobacco mediated oral carcinogenesis and acts as a potent cyclin dependent Kinase 4 Regulatory Factor (KRF) and a potential cancer target [92].…”
Section: Discussionmentioning
confidence: 99%